2013
DOI: 10.3758/s13415-013-0230-2
|View full text |Cite
|
Sign up to set email alerts
|

Beauty is in the ease of the beholding: A neurophysiological test of the averageness theory of facial attractiveness

Abstract: Multiple studies show that people prefer attractive over unattractive faces. But what is an attractive face and why is it preferred? Averageness theory claims that faces are perceived as attractive when their facial configuration approximates the mathematical average facial configuration of the population. Conversely, faces that deviate from this average configuration are perceived as unattractive. The theory predicts that both attractive and mathematically averaged faces should be processed more fluently than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
66
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 80 publications
(76 citation statements)
references
References 107 publications
9
66
1
Order By: Relevance
“…By contrast, artificially modified (stretched) unattractive faces affected P1 and P2 amplitudes, rather than the N170. Along similar lines, another study (Trujillo, Jankowitsch, & Langlois, 2014) observed a smaller N170 for more attractive, as well as averaged faces, compared to less attractive faces. This suggested that the N170 might in fact be sensitive essentially to the typicality of a face (i.e.…”
Section: Discussionsupporting
confidence: 52%
“…By contrast, artificially modified (stretched) unattractive faces affected P1 and P2 amplitudes, rather than the N170. Along similar lines, another study (Trujillo, Jankowitsch, & Langlois, 2014) observed a smaller N170 for more attractive, as well as averaged faces, compared to less attractive faces. This suggested that the N170 might in fact be sensitive essentially to the typicality of a face (i.e.…”
Section: Discussionsupporting
confidence: 52%
“…32,33 In the present study, the ERPs in the incongruent condition expectedly showed larger negativity N2 in comparison with those in the congruent condition. A similar study also found that an incongruent condition elicits a much more negative deflection (N300) than incongruent stimuli.…”
Section: Behaviormentioning
confidence: 72%
“…Researchers have found that neural activities related to attractiveness perception are engaged even when participants are not explicitly asked to judge it (Aharon et al, 2001; Trujillo, Jankowitsch, & Langlois, 2014), which furthers the argument that EMG can be used to reliably assess differential reactions from participants. Specifically, attractiveness effects have been found in the activation of zygomaticus major (ZM; pulling the corner of the lips into a smile; a positive affect response) and unattractiveness effects in the activation of corrugator supercili (CS; knitting the brow; a negative affect response) and levator labii superioris (LLS; raising the nostril; a disgust response) (Gerger, Leder, Tinio, & Schacht, 2011; Principe & Langlois, 2011).…”
Section: Measuring Affect: Electromyographymentioning
confidence: 87%